2008
DOI: 10.3354/dao01917
|View full text |Cite
|
Sign up to set email alerts
|

Association and distribution of the ciliate Orchitophrya stellarum with asteriid sea stars on the west coast of North America

Abstract: The association of the scuticociliate Orchitophrya stellarum with 3 species of asteriid sea stars from the west coast of North America was studied by flushing the gonopore region with seawater and spawning the sea stars, along a latitudinal gradient of 2549 km between Pigeon Point, California, and Kodiak, Alaska. Asterias forbesii and A. rubens from the Isles of Shoals, New Hampshire (east coast), were also sampled. The ciliate was found on the aboral surface of both sexes of reproductively ripe Evasterias tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, sex or size-biased mortality from wasting disease can not explain the heavily skewed sex ratios in Vancouver Island populations (e.g. Stickle & Kozloff 2008). Leighton et al (1991) proposed that the emerging ciliate parasite Orchitophyra stellarum found infecting the testes of male sea stars drives male-biased mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sex or size-biased mortality from wasting disease can not explain the heavily skewed sex ratios in Vancouver Island populations (e.g. Stickle & Kozloff 2008). Leighton et al (1991) proposed that the emerging ciliate parasite Orchitophyra stellarum found infecting the testes of male sea stars drives male-biased mortality.…”
mentioning
confidence: 99%
“…We also conducted experiments to compare the progression of wasting disease in specimens collected in early versus late summer, and from localities that varied in wave exposure. Because Pisaster populations on Vancouver Island are heavily female-biased at larger size classes (Leighton et al 1991, Stickle & Kozloff 2008, we also tested for sex or size-biased infection. …”
mentioning
confidence: 99%